PENERAPAN MODEL PEMBELAJARAN KOOPERATIFTIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) UNTUKMENINGKATKAN HASIL BELAJAR PKn KELAS VSD NEGERI 011 BUKIT GAJAH KECAMATAN UKUI - Jasman R ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this research by studying PKn low yields, it is characterized by the acquisition value of the average student at 67.2 it is still by far the KKM set that is equal to 75. In addition, only 9, or 37.80% of students who completed study results, Based on this the researchers want to improve learning through action research by applying cooperative learning model type STAD. This study dilakasanakan as much as two cycles each consisting of two meetings and one daily tests. The subjects were fifth grade students of SD Negeri 011 Bukit Gajah. Data collection techniques used observation techniques as well as the activities of teachers and students learn PKn test results. The study states that the implementation of cooperative learning model STAD can drive the Civic Education student learning outcomes. This is evidenced by: (a) the activities of teachers at each cycle has increased. In the first cycle of the first meeting activity for teachers to get a score of 15 or 62.5% in both categories. In the first cycle of meetings II activity learn obtain a score of 19 or 79.2% in both categories, the second cycle of the first meeting of the activity the teacher obtained a score of 22 or 91.7% with very good category. On the activities of teachers given a score of 23 or 95.8% with very good category. Activities of students in each cycle has increased. In the first cycle of the first meeting of student activity obtained a score of 13 or 54.2% to the category enough. In the first cycle of meetings II activities of students obtained a score of 17 or 70.8% in both categories, the second cycle of the first meeting of student activity obtained a score of 20 or 83.3% with very good category. On the activities of students obtained a score of 21 or 87.5% with very good category; and (b) the learning outcomes of students has increased. This is demonstrated by the average student learning outcomes has increased, ie the first cycle increased to 13.1% from 67.2 into 77.3 base score at UH cycle I. In the second cycle increased by 24.7% from a base score of 67, UH 2 to 83.8 in the second cycle. Classical completeness increased, on a base score of 37.8% increase in the first cycle to 71.1% and the second cycle increased to 93.3%.